Kemajuan Material Komposit Berbasis Termoplastik untuk Helm Balistik yang Ringan dan Berkinerja Tinggi - Nabila Zahira Nasution; Sovian Aritonang (Fakultas Teknik UMSU, 2026)
The advancement of modern material technology has driven innovation in ballistic protection, particularly in the development of lightweight yet high-performance helmets for military and law enforcement applications. One of the main focuses of current research is the use of thermoplastic-based composite materials as an alternative to conventional thermoset composites such as epoxy–Kevlar. Thermoplastic composites—such as polyether ether ketone (PEEK), polypropylene (PP), and polyamide (PA)—offer several advantages, including high toughness, recyclability, and ease of fabrication through thermoforming or compression molding techniques. In terms of the state of the art, numerous studies have demonstrated significant improvements in impact energy absorption and penetration resistance in ballistic helmets reinforced with aramid, UHMWPE, or carbon fibers combined with thermoplastic matrices. However, most research still focuses on individual mechanical testing without a comprehensive approach to the influence of fabrication parameters, fiber–matrix compatibility, or the correlation between microstructural characteristics and ballistic performance. The identified research gap lies in the absence of a systematic review that integrates the latest findings to map trends, technical challenges, and research directions for developing thermoplastic composite materials as optimal solutions for lightweight, ergonomic, and high-performance ballistic helmets. This study aims to identify, evaluate, and critically synthesize the recent advancements in thermoplastic-based composite materials for ballistic helmet applications, emphasizingmechanical performance, ballistic resistance, and material sustainability potential. Furthermore, this research seeks to formulate recommendations for future research directions in the development of head protection systems utilizing thermoplastic composite materials. The methodology employed is a Systematic Literature Review (SLR) with a descriptive-analytical approach based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta- Analyses) guidelines. The SLR process includes identification, selection, quality assessment, and synthesis of data from relevant scientific publications published over the past two decades. Through this approach, the study is expected to produce a comprehensive mapping of trends, challenges, and innovation opportunities in the development of lightweight, durable, and sustainable thermoplastic composite-based ballistic helmets.